Robust quadratic assignment problem with budgeted uncertain flows - Mohammad Javad Feizollahi; Hadi Feyzollahi (Operations Research Perspectives, 2015)
We consider a generalization of the classical quadratic assignment problem, where material flows between facilities are uncertain, and belong to a budgeted uncertainty set. The objective is to find a robust solution under all possible scenarios in the given uncertainty set. We present an exact quadratic formulation as a robust counterpart and develop an equivalent mixed integer programming model for it. To solve the proposed model for large-scale instances, we also develop two different heuristics based on 2-Opt local search and tabu search algorithms. We discuss performance of these methods and the quality of robust solutions through extensive computational experiments.
Keywords: 330; Robust optimization; Budgeted uncertainty; Quadratic assignment problem; 2-Opt; Tabu search